Teologia do corpo em Adélia Prado : uma proposta religiosa transgressora - Santos, Itania Mara (2019)
The present research is the result of constant concerns about the theological conception regarding the body present in the work of Adélia Prado. We qualify this conception as “transgressive” in virtue of the freedom and daring with which the theme is treated in his poetry, mainly those that have religious references. The general objective of the present study is to understand how Adélia Prado places the body as a sacred place, source of religious and poetic experience, trying to identify the mechanisms used by the author to exempt herself from the dichotomous vision consolidated in Christian thought and society. This formulation has as hypothesis the uncovering of the sexuality of a lady and a religious lyrical subject; as well as, despite demonstrating theological knowledge and the dogmas of her religion, her poetry does not corroborate with religious formulations. At the same time, the poetess does not break with her Christian tradition. Our journey in the first instance is about the interlacing between theology and literature; the second part of this proposal presents, although brief, a historical study on the itinerary of the female body in the Catholic Church regarding the exercise of sexuality, considering the history of the body from a feminist point of view, both Catholic and Protestant. And finally, the third and final chapter we expose, based on the poetic art of Adélia Prado writer, as issues concerning the body and sexuality appear in your resignified work. Therefore, this research brings in its methodology the obtaining of historical data. First, a bibliographical hermeneutic survey will be done in order to obtain a current result with new and relevant data for the studies within this thematic that approaches the literary work of Adélia Prado. For this analysis, we will make use of several theoretical contributions. In the end, the dissertation concludes that, although Christian tradition belittles erotic desires, especially feminine, leading theology to marginalize the issues related to the body, Adélia Prado’s work subverts this conception from poetry, electing the body as a space of experience of spirituality and the resignification of the sacred.